Issues Of Light and Illumination in Uzbek Feature Films - Kadirov Behzod Bahodirovich; Karimova Kigora G’anievna (Genius Journals, 2023)
The article considers the role and function of light in the visual interpretation of Uzbek feature films, consideration of its nature and features, comprehension of its essence in the visual layer of classic and currently created digital films. The need to apply digital film technology to the traditional process of film production, study and analysis of the function of light and refreshment in the production of artistic-aesthetic and technological films of new format becomes clear.
Keywords: Lighting; cinema; operator’s art; frame